Exports and Jobs for Inclusive Growth in Cambodia - Deeksha Kokas; Jaime Alfonso Roche Rodriguez; Gladys Lopez-Acevedo; Raymond Robertson; Wendy Karamba (Institute of Labor Economics (IZA), 2024)
Cambodia's rapid economic growth in the past few decades has coincided with trade liberalization and structural transformation. This growth has been extensively associated with more employment, higher wages, shared prosperity, and poverty reduction. By combining two complementary approaches, the Gravity model and the Bartik model, this paper estimates: (i) the relationship between trade agreements and trade flows, and (ii) the relationship between trade exposure and various local labor market outcomes. Our gravity estimates show that trade agreements between the Association of Southeast Asian Nations (ASEAN) are positively related with trade flows, and that Cambodia's specific gains from these increases in trade have been larger than for the average trade agreement. This has led to better results for workers in Cambodia's local labor markets. Our shift-share Bartik results suggest that increases in trade exposure in Cambodian districts between 2009 and 2019 correlate with reduced informality and an increase in hours worked, with more positive effects for female workers.
Keywords: 330; trade policy; exports; trade exposure; employment; informality; wages